Wheel Access Does Not Attenuate Weight Gain in Mice Fed High-Fat or High-CHO Diets - Jung, Alan P. (2010)
PURPOSE: To determine the effect of a high-fat or high-carbohydrate diet and running wheel activity on body composition, body mass, and caloric intake in C57Bl/6 mice. METHODS: At four weeks of age, five groups of C57Bl/6 mice were housed individually. Two groups had running wheels, while the other three groups did not. Within the running wheel groups, FAT-W consumed a high-fat diet (60.3% fat) and CHO-W consumed a high-carbohydrate diet (70.4% carbohydrate). Within the non-running groups, FAT consumed the high-fat diet, CHO consumed the high-carbohydrate diet, and CON consumed standard chow. All groups consumed food ad libitum, and were exposed to their respective conditions for 12 weeks. Wheel activity, food consumption, body mass (BM), and body fat (%BF) were recorded. RESULTS: There was no significant difference in %BF or BM at the end of 12 weeks between FAT-W and FAT or between CHO-W and CHO (p>0.05). %BF was significantly higher in both FAT-W (42.9±0.6%) and FAT (45.9±0.8%) compared to CHO-W (30.8±1.4%) or CHO (33.4±1.0%; p<0.001). BM was significantly higher in both FAT-W (42.8±0.7g) and FAT (44.7±1.2g) compared to either CHO-W (32.8±1.6g) or CHO (37.1±0.8; p<0.01). There was no difference in wheel activity between FAT-W and CHO-W (p>0.05). Daily caloric intake was higher in both FAT-W (17.0±0.8kcal) and FAT (15.9±0.9kcal) compared to CHO-W (13.9±0.7kcal) and CHO (13.6±0.5kcal; p<0.01). CONCLUSION: Access to a running wheel had no protective effect on BM or %BF in C57Bl/6 mice that consumed either a high-fat or high-carbohydrate diet over a 12-week period. Access to a running wheel did not affect caloric intake; however, average daily caloric intake was higher in mice on high-fat diets compared to mice on a high-carbohydrate diet.